Breast Cancer: Knowledge, Attitude and Practice of OCI CerviBreast App Campaign Message on ABS 88.5 FM, Awka, Among Undergraduate Students of Nnamdi Azikiwe University - Ezeonyejiaku, Njideka Patience; Onyejelem, Timothy Ekeledirichukwu; Nwokeocha, Ifeanyi Martins (International Journal of Religion Education and Law, 2025)
Background: Breast cancer remains one of the leading causes of death among women in their productive years worldwide. Despite advances in treatment, prevention continues to be the most effective strategy to reduce mortality rates. Health communication campaigns across various media platforms play a vital role in educating and sensitizing the public on preventive measures. One such campaign is the OCI CerviBreast App Campaign, broadcast on ABS 88.5 FM, Awka.Objectives: This study aims to assess the level of awareness, attitude, and practice related to the OCI CerviBreast App campaign message among undergraduate students at Nnamdi Azikiwe University, Awka. Specifically, the research examines students' exposure to the campaign, evaluates their knowledge of breast cancer prevention, and investigates their attitudes and practices regarding the recommended preventive techniques.Theoretical Framework: The study is anchored on the Health Belief Model (HBM), which explores individuals’ perceptions of health threats and the benefits of preventive actions, and the Digital Generative Multimedia Tool Theory (DGMTT), which emphasizes the role of digital media in health communication.Method: A survey research design was employed to gather data from undergraduate students of Nnamdi Azikiwe University. The questionnaire assessed exposure to the campaign message, knowledge of self-breast examination steps, attitudes towards breast cancer prevention, and actual practice of recommended preventive techniques.Results: Findings indicate that a significant proportion of students have heard the campaign message on ABS Radio. However, less than half could recall the specific steps for breast self-examination. Additionally, more than half of the students are yet to practice the preventive techniques promoted in the campaign.Conclusion: Although the radio campaign effectively raises awareness, there is a gap between awareness and the retention and practice of preventive measures among students. Enhancing engagement and comprehension is essential to translate awareness into actionable practice.Unique Contribution: This study uniquely combines the application of the Health Belief Model and the Digital Generative Multimedia Tool Theory to evaluate the impact of a radio-based health campaign in a university setting, highlighting the need for diverse communication strategies to reach young adults effectively.Key Recommendations: It is recommended that a multi-media approach be adopted, leveraging online platforms and social media to reach the predominantly digital-native undergraduate population. Such strategies could improve message retention, understanding, and the adoption of preventive behaviours.